Towards developing methods to increase uptake of palladium by plants for revegetation and remediation of mine wastes - Shamsul Harumain, Zakuan Azizi (Kansas State University Manhattan, Kansas State, US, 2015)
Waste materials (tailings) generated from mining processes contain significant amounts of palladium, which are considered uneconomical to be extracted using conventional methods. Studies have demonstrated that Arabidopsis thaliana (Arabidopsis) can accumulate palladium as nanoparticles in the plant tissues. In collaboration with the Green Chemistry Centre of Excellence at the University of York, we have recently demonstrated that this nanoparticle rich material can be used as a high-value catalyst, without the need to extract the metals from the plant biomass [1]. One of the properties of palladium is that it occurs naturally in the zero valent form. This represents a problem for phytoextraction as transition metals are usually taken up by plants as cations. To overcome this problem phytoextraction of gold, which is chemically similar to palladium, uses cyanide-based methods to promote gold solubility in soil. The use of cyanogenic compounds is not a long-term, environmentally sustainable method for palladium phytoextraction. Alternative methods may come from a greater understanding of the biological processes involved. Our studies have identified genes that are strongly regulated by gold, including a discreet suite of divalent metal cations [2]. We are now extrapolating these investigations to palladium to investigate solubilisation, uptake and nanoparticle formation of palladium in plants.